The Specific Features Of The Transport Policy Of The Republic Of Uzbekistan - Umarali Xabibulla o‘g‘li Gulmatov (Periodica Journal, 2024)
This article discusses the transport policy being implemented in Uzbekistan and its unique features, with a particular focus on the role of the regulatory documents introduced in the development of the sector. Additionally, the article addresses several issues inherited from the Soviet era and provides suggestions for their resolution. В данной статье освещена транспортная политика, осуществляемая в Узбекистане, а также её особенности, с особым вниманием к роли нормативных документов в развитии отрасли. Кроме того, рассмотрены детали ряда проблем, унаследованных с советских времён, и предложены пути их решения.
Keywords: Road transport; aviation transport; railway transport state policy